Asmaul Husna-Based Walking Therapy: Autoethnography in the Perspective of Spiritual Psychology - Puji Astuti Indraningsih (Green Publisher Indonesia, 2025)
This research aims to describe and reflect on the experience of self-healing through the practice of walking therapy based on Asmaul Husna. Using an autoethnographic approach, the author narrates the inner journey of being a single mother and epilepsy survivor in the face of chronic life stress. The results of the study show that the practice of walking while reciting Asmaul Husna not only has a positive impact physically, but also opens up the space of spiritual awareness, strengthens psychological resilience, and builds a transcendental connection with God. Asmaul Husna's dhikr becomes an inner anchor that helps to unravel stress and strengthen the meaning of life. This study recommends the integration of spiritual-local approaches in contemporary psychological interventions, particularly those related to stress recovery and inner well-being.